2019
DOI: 10.1093/nar/gkz522
|View full text |Cite
|
Sign up to set email alerts
|

Study of conformational transitions of i-motif DNA using time-resolved fluorescence and multivariate analysis methods

Abstract: Recently, the presence of i-motif structures at C-rich sequences in human cells and their regulatory functions have been demonstrated. Despite numerous steady-state studies on i-motif at neutral and slightly acidic pH, the number and nature of conformation of this biological structure are still controversial. In this work, the fluorescence lifetime of labelled molecular beacon i-motif-forming DNA sequences at different pH values is studied. The influence of the nature of bases at the lateral loops and the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…The i-motif is a unique DNA quadruplex structure formed by inserting two cytosine-rich duplexes into each other in an antiparallel manner only in an acidic environment. It has been reported that in an acidic microenvironment ( 50 , 51 ), nano-hydrogels can be internalized by cells to form an i-motif, which is decomposed in lysosomes ( 52 , 53 ), and the mRNA is then released into the cytoplasm to express the encoded protein. These systems include no chemical agents, so the structure is biocompatible.…”
Section: Mrna Delivery Systemsmentioning
confidence: 99%
“…The i-motif is a unique DNA quadruplex structure formed by inserting two cytosine-rich duplexes into each other in an antiparallel manner only in an acidic environment. It has been reported that in an acidic microenvironment ( 50 , 51 ), nano-hydrogels can be internalized by cells to form an i-motif, which is decomposed in lysosomes ( 52 , 53 ), and the mRNA is then released into the cytoplasm to express the encoded protein. These systems include no chemical agents, so the structure is biocompatible.…”
Section: Mrna Delivery Systemsmentioning
confidence: 99%
“…I tail and I cap are each designed to contain an i-motif sequence, which can hybridize with X tail and X cap respectively under a neutral or alkaline environment, and de-hybridize to fold into an i-motif structure under an acidic condition. [28,37] (Scheme 1c) Therefore, the nano-hydrogel is pH-responsive. It is expected to maintain the nanostructure in a physiological environment outside cells, and disintegrate to release mRNA for the expression of encoded proteins when it enters into lysosome (pH 4.5-5.0) of cells through endocytosis.…”
Section: Principle Of the Mrna Delivery By The Ph-responsive Dna Nano-hydrogelmentioning
confidence: 99%
“…I-motif, a specific DNA quadruplex structure, is formed only in an acidic environment by two cytosine-rich double-strands being inserted into each other in antiparallel. [27,28] After being internalized by cells, with the formation of i-motif, the nano-hydrogel can disintegrate in the lysosome, which has been widely reported to have an acidic microenvironment with a pH of 4.5-5.0, [29,30] and thereby release the mRNA into the cytoplasm to express the coded protein. The architecture has excellent biocompatibility since that no chemical materials are used, and in parallel, is stable because it maintains a well-defined structure outside the cells and disintegrates only at low pH inside the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-induced pH shift refers to the pH shift caused by the reaction of photosensitive substances under the light condition, thus transforming the structure of DNA. Zhao et al [ 98 ] fixed the photosensitive substance malachite green (MGCB) at the nanochannels of MSN, and the i-motif DNA structure was grafted onto the surface of MSN to seal the orifice; i-motif was a special DNA four-chain structure, and only when two cytosine-rich double-chains were inserted antiparallel in an acidic environment could i-motif be formed [ 99 , 100 ]. Under UV light, MGCB was dissociated into malachite green (MG) cation and OH - ion so that the pH of the solution increased, followed by the i-motif structure being converted into a single chain and the guest molecule being released [ 98 ].…”
Section: Intelligent-responsive Dna Nanodevicementioning
confidence: 99%